Pengelolaan Ekowisata Halal (Halal Ecotourism) di KabupatenMojokerto dalam Perspektif Fiqh Bi’ah - Farah Nur Fauziah (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2021)
Indonesia is an archipelagic country and has diverse cultures and tribes and isscatteredin various regions. This wealth makes Indonesia a very large tourism wealth. With thedevelopment of halal tourism in Indonesia, we need to think about environmentalimpacts. Environmental preservation is known as environmental fiqh (fiqhul bi`ah). Itis hoped that the concept of fiqh bi'ah can be used as a basis in managing halalecotourism in Mojokerto district. This research method is qualitative. The way ofcollecting data in this research is by literature study and observation. The results ofthis study indicate the importance of fiqh bi'ah as a basis for thinking in managinghalal ecotourism in Mojokerto district. This is due to the very rapid growth of tourismin Mojokerto district so that it needs synergy towards the environment.